Implementation of output impedance in single-phase inverters with repetitive control and droop control - Astrada, Juan Carlos (2020)
A strategy for the implementation of the output impedance in single-phase inverters connected in parallel with droop control for uninterruptible power supply applications is proposed in this study. The proposal allows the load current to be distributed in proportion to the power capacity of the inverters connected in parallel, by establishing the magnitude and phase of the output impedance at the fundamental frequency and its harmonics, when the voltage control is performed through odd harmonic repetitive controllers. This is accomplished through the design of an output impedance profile based on the transfer function of a second-order high-pass filter and a virtual impedance loop. The proposal achieves a correct operation of the droop control strategy and the proper sharing of the harmonics of the non-linear load current between the inverters connected in parallel, obtaining reduced values of individual harmonic content and harmonic distortion in the output voltage with reduced processing requirements. The validity of the proposal is verified through a 2 kVA experimental prototype, considering the requirements of the international quality standards IEC62040-3 and IEC61000-2-2, in terms of output voltage regulation, individual harmonic content, and harmonic distortion for inverters operating both in islanded-mode and in parallel.